“According to social media…” Examining the influence of social media on political reporting within Zimbabwe’s mainstream media - Ndou, Delta Lau Milayo (Centre for Film and Media Studies, 2020)
The Internet’s liberative qualities have been hyped by a number of Zimbabwean scholars who argue, on the basis of the existence of online alternative media that carries political content, that democratisation can be technology-led. Given that the question of source selection is connected to the democratising potential of the Internet (Lecheler and Kruikemeier, 2016) by some scholars – this study interrogated the liberative potential of the Internet by tracing the social media sourcing patterns of four daily newspapers within Zimbabwe’s polarised mainstream media. Using a mixed methods approach which deployed Actor-Network theory as a preliminary methodological tool, this study collected and evaluated empirical data drawn from 146 social media sourced political stories published over a 30-month period and the responses from semi-structured interviews with purposively sampled participants – to account for the human and non-human actors in the news production network. A social constructivist analytical lens was then used to appreciate the contexts in which social media sourcing was being adopted in newsrooms, which revealed how unique circumstances had triggered unprecedented reliance on social media as a political news source. Those unique circumstances involved an escalation of factional fighting within the ruling ZANU PF that morphed into a propaganda war, which was waged through The Herald newspaper by one faction and through social media by the other faction. The public feud, which played out on social media, forced political reporters to gather story ideas from social media and overly rely on a few tech savvy elite sources. In these circumstances, social media’s influence on the political news agenda was overstated as it was conflated with the influence of a news event (ZANU PF factionalism) and the influence of social media users (high-ranking ZANU PF members) who could not be ignored. It is hoped that the findings of this study will contribute towards filling the lacuna in terms of scholarship demonstrating the influence of social media within Zimbabwe’s political narratives.